FAKTOR – FAKTOR BERHUBUNGAN DENGAN STATUS GIZI KURANG PADA ANAK BALITA DI POSYANDU MELATI WILAYAH KERJA PUSKESMAS KOTA BAMBU SELATAN - Vionalita, Gisely; Sari, Ratih Novita (Jurnal Nutrire Diaita (Ilmu Gizi), 2019)
The data shows that the finding of malnutrition case happened at Posyandu Melati of South Bamboo City Public Health Center, this also always increase, it can be seen from number of cases in April that is 8 children with malnutrition status and 2 children with malnutrition status. While in May there was an increase in the case of malnutrition to 9 children, the incidence of malnutrition incidence is zero case. The purpose of this study was to analyze the factors - factors associated with the occurrence of nutritional status is less in children under five. This type of quantitative research uses case control design. This research was conducted on June 26, 2018. The research sample used a ratio of 1: 3, with a sample case of 11 people and a control sample of 33 people. Data collection using questionnaires. The statistical test used Chi-Square test. Based on the result of Chi-Square test showed that the exclusive breastfeeding was related to the lack of nutritional status (p = 0,002), the number of family member was not related to the malnutrition (p = 0,486), the family income was not related to the malnutrition status (p = 0,014), education level is related to nutrient status less (p = 0,004), compliance of weighing is related to nutritional status (p = 0,002), suggestion that can be done is the addition of activity that can motivate mother in exclusive breastfeeding, and increasing frequency of posyandu implementation. Keywords: nutritional status, children under five, posyandu